Assessing impacts of declines in the world price of tobacco on China, Malawi, Turkey, and Zimbabwe - Diao, Xinshen; Robinson, Sherman; Thomas, Marcelle; Wobst, Peter (International Food Policy Research Institute, 2002)
This study quantitatively analyzes the general equilibrium effects of declines in world demand for tobacco products. The study finds that tobacco exports and production in the three developing countries, Malawi, Zimbabwe, and Turkey, would be badly hit if world tobacco prices fall due to the decline in tobacco demand. Moreover, for a given decrease in the world tobacco price, the more important the tobacco sector is in an economy, the worse the tobacco sector is hit. Tobacco is quite important to the Malawian and Zimbabwean economies as tobacco production and trade accounted for, respectively, 17% and 43% of agricultural GDP and tobacco exports accounted for 50% and 35% of national exports in these two countries. The negative effects of a decline in world tobacco prices on the Malawian and Zimbabwean economies are much larger than that on the Turkish economy. In the case of China, tobacco production, marketing, cigarette processing, distribution, and foreign trade are strictly controlled by the government and tobacco trade accounted for a small share of production and consumption. Thus, the decline in the world tobacco prices would hardly affect China’s tobacco sector. The study shows that it is highly risky for a developing country to highly depend on exports of a single agricultural commodity. To reduce such risk, a country has to create a more diversified and flexible export structure.